The Attachment of Adolescent with Working Mother - Enung Huripah; Meilani Dewi Setiamanah; Rohman Rauf Alfansuri (Indonesian Journal of Social Work, 2017)
Adolescence is often called the preparation period for becoming adult where individually they act and behave and grow into adulthood. The successful development process of adolescent to adulthood depends on care and guidance from people in their family or parents especially mother. The research focus was aimed to analyse the attachment of adolescent with working mother. The purpose of the research was to analyse characteristic, attachment of adolescent with working mother, the relationship and meeting intensity between adolescent and working mother. This research used qualitative approach. Data resource consisted four working mothers and four adolescents who have working mother. Data collection technique used in-depth interview, passive participation observation and documentation study. The analysis stage covering data reduction, data presentation and conclusion. The result showed that the attachment of adolescent with working mother have differences between one family and another. Factors that may affect attachment intensity differences between adolescent with working mother covering; history of child care using caregiver or housemaid; awareness and understanding of adolescent and working mother respective activities; and alternative effort which is conducted by adolescent and working mother to overcome that obstruct communication.